Description of cases of child sexual violence in indonesia from 2018 to 2022 (literature review) - A Rusman, Andri; Ismail, Mirza; Salman, Adam (ACTA Medical Health Sciences, 2024)
Sexual violence against children in Indonesia has been a pervasive issue that largely remains concealed, resembling the phenomenon of an iceberg. The Indonesian Child Protection Commission (KPAI) reported that there was a significant increase in the number of children who were victims of sexual violence in 2020. Children are particularly vulnerable to such violence, as they are often perceived as weak or powerless and are highly dependent on the adults in their environment. This study aims to describe cases of sexual violence against children in Indonesia from 2018 to 2022. The type of this research is a descriptive study, using a literature review approach by searching for various relevant sources through Google Scholar and Publish or Perish databases. The keywords used in the research for relevant articles include violence, sexual violence, child sexual violence, victims, perpetrators, risk factors. A total of 17 articles were selected for analyses using a synthesis matrix, obtaining following results: (1) The majority child victims of sexual violence were aged 12 to under 18 years old and were predominantly female; (2) Most perpetrators of sexual violence were over 18 years of age and predominantly male; (3) A significant number of perpetrators were part of extra-familial groups; (4) The most prevalent form of sexual violence was penetration, (5) Most the risk factors for sexual violence were associated with familial aspects. DOI : 10.35990/amhs.v3n2.p91-105 REFERENCES Komisi Perlindungan Anak Indonesia. (2021). REFERENCES1.2021. Darus, D. N., & Permana, R. (2022). Kekerasan seksual terhadap anak: Bentuk kekerasan seksual pada anak dan pelaku kekerasan seksual pada anak. [Jurnal tidak disebutkan], 400–407. Jannah, N., & Irfani, A. (2021). Peran Komisi Perlindungan dan Pengawasan Anak Daerah Provinsi Kalimantan Barat dalam penanganan kekerasan seksual pada anak tahun 2021. Ilmu Bimbing Konseling Islam, 01(2), 48–56. Ivo, N. (2015). Kekerasan seksual terhadap anak: Dampak dan penanganannya. Sosio Info, 01(200), 13–28. Adnyana, I. G. H. E. (2021). Karakteristik kasus pada Visum Et Repertum dengan dugaan kekerasan seksual di RSUP Sanglah Denpasar. Jurnal Kedokteran, IX(1), 1248–1256. Arsawati, N. N. J., & Antari, P. E. D. (2021). Antitesis pemenuhan hak anak korban kekerasan seksual dalam sanksi adat: Studi di Desa Tenganan, Karangasem. Jurnal Magister Hukum Udayana, 10(1), 104. Rini, R. (2020). Dampak psikologis jangka panjang kekerasan seksual anak. IKRA-ITH Humaniora, 4(3), 1–12. Wismayanti, Y. F., O’Leary, P., Tilbury, C., & Tjoe, Y. (2019). Child sexual abuse in Indonesia: A systematic review of literature, law and policy. Child Abuse & Neglect, 95, 104034. https://doi.org/10.1016/j.chiabu.2019.104034 Rumble, L., Febrianto, R. F., Larasati, M. N., Hamilton, C., Mathews, B., & Dunne, M. P. (2020). Childhood sexual violence in Indonesia: A systematic review. Trauma, Violence, & Abuse, 21(2), 284–299. https://doi.org/10.1177/1524838018767932 Agustina, P. W., & Kusumaning Ratri, A. (2018). Analisis tindak kekerasan seksual pada anak sekolah dasar. Jurnal Kajian Teori dan Praktik Kependidikan, 3(2), 151–155. Noviani, P. U., Arifah, R., Cecep, C., & Humaedi, S. (2018). Mengatasi dan mencegah tindak kekerasan seksual pada perempuan dengan pelatihan asertif. Prosiding Penelitian dan Pengabdian kepada Masyarakat, 5(1), 48. Latjengke, A. P., Tomuka, D., & Kristanto, E. G. (2020). Gambaran kasus kejahatan kekerasan seksual di RS Bhayangkara Tingkat III Manado periode Januari 2017–Desember 2019. e-CliniC, 8(2). Suwandi, J., Chusniatun, C., & Kuswardani, K. (2019). Karakteristik kekerasan seksual terhadap anak perempuan di Wonogiri dan Boyolali. Jurnal Pendidikan Ilmu Sosial, 29(1), 65–77. Kusuma, A. P. U., Nasution, A., & Saputra Nasution, A. (2021). Faktor-faktor yang mempengaruhi kejadian kekerasan seksual terhadap siswa di SMA Muhammadiyah Kota Bogor. Promotor, 4(3), 192–198. https://ejournal.uika-bogor.ac.id/index.php/PROMOTOR/article/view/5586 Sulastri. (2018). Kekerasan seksual terhadap anak Indonesia. Jurnal Psikologi Malahayat, 1(2), 61–71. Scarvanovi, B. W. (2020).